+0  
 
0
88
3
avatar+29 

let p(x) = x^2, q(x) = 2x^3+1, and r(x) = 7x^4 - 5x^3 - 6x - 2. Find p(q(x)) + r(x)

 

ty in advance :)

 Jun 4, 2021
 #1
avatar+179 
0

\(4x^6+7x^4−x^3−6x−1\)

.
 Jun 4, 2021
 #2
avatar+2205 
0

Hello, welcome to web2.0calc. :))

 

=^._.^=

catmg  Jun 4, 2021
 #3
avatar+780 
0

Let $p(x) = x^2, q(x) = 2x^3+1,$ and $r(x) = 7x^4 - 5x^3 - 6x - 2.$ Find $p(q(x)) + r(x).$

We have $(2x^3 + 1)^2 + (7x^4 - 5x^3 - 6x - 2) = 2x^6 + 4x^3 + 1 + 7x^4 - 5x^3 - 6x - 2 = \boxed{2x^6 + 7x^4 - x^3 -6x - 1}.$


54 Online Users